Complementary and alternative medicine sourcebook : basic consumer health Information about ayurveda, acupuncture, aromatherapy, chiropractic care, diet-based therapies, guided imagery, herbal and vitamin supplements, homeopathy, hypnosis, massage, meditation, naturopathy, pilates, reflexology, Reiki, Shiatsu, Tai Chi, traditional Chinese medicine, yoga, and other complementary and alternative medical therapies ; along with statistics, tips for selecting a practitioner, treatments for specific health conditions, a glossary of related terms, and a directory of resources for additional help and information - 4 0 16; (Editor of health information), Hayes, Kevin; 5 (Detroit, MI : Omnigraphics, Inc., 2022)
Provides basic health information on complementary and alternative medicine therapies, including dietary supplements, biologically based therapies, mind-body medicine, manipulative and body-based therapies, and energy-based therapies, along with facts about alternative treatments for specific diseases and conditions. Includes index, glossary of related terms, and other resources--
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; Alternative medicine -- 20 -- Popular works; 20; 2